Gender Influence on the Organizational Silence in the School Sector in Amman, Jordan. - MOHAMMED AL ZOUBI, MUNIF; KHALED ALKHLAIFAT, OSAMA (International Journal of Psychosocial Rehabilitation, 2024)
This research is based on the the school sector in the Jordanian Capital Amman and aims to measure the difference in the silence level between teachers according to gender and to determine which silence’s factors have an impact on the decision-making process. A questionnaire was distributed to collect the information needed from a study sample of 1643 male and female teachers that were randomly selected. The required tests were carried out to ensure the reliability of the questionnaire. Furthermore, the correlation coefficient and multiple regression analysis was used to test the hypotheses of the study. According to some of the results there was a moderate difference in the silence level between genders, and there was an inverse relationship between the factors of silence and participation in decision-making. Moreover, the results showed that the organizational silence level is higher in female teachers than in male ones. Furthermore, the results showed that female teachers are higher in each silence factor except for psychological withdrawal